Efficient market hypothesis in emerging markets: Panel data evidence with multiple breaks and cross sectional dependence - Ahmad, AH; Daud, SNM; Azman-Saini, WNW (Economics Bulletin, 2024)
The purpose of this paper is to re-examine whether mean reversion property hold for 15 emerging stock markets for the period 1985 to 2006. Utilizing a panel stationarity test that is able to account for multiple structural breaks and cross sectional dependence, we find that the emerging stock markets follow a random walk process. However, further analysis on individual series show that the majority of stock prices in emerging markets are governed by a mean reverting process. This result, which is inconsistent with efficient market hypothesis, suggests that past information is useful in predicting future prices in most of the markets.